Complex effects of IL1A polymorphism and calpain inhibitors on interleukin 1a (IL-1a) mRNA levels and secretion of IL-1a protein - Lee, S.; Temple, S.; Roberts, S.; Price, Patricia (Blackwell Munksgaard, 2008)
Alleles of IL1A-889(C>T) and IL1A+4845(G>T) are in linkage disequilibrium. Interleukin 1a (IL-1a) is produced as a precursor protein and cleaved at positions 117-118 by calpain, generating a mature protein for export. IL1A+4845 affects amino acids expressed at position 114 and hence may modulate calpain-mediated cleavage. We sought evidence for this mechanism in intact cells. Blood leukocytes from heterozygous donors released more IL-1a protein than cells from IL1A(1,1) donors, while release from IL1A(2,2) cells was variable. Genotype did not affect levels of IL-1a mRNA, so differential cleavage of the precursor is a feasible mechanism. However, genotype also had no effect on inhibition of IL-1a release by pretreatment with calpain inhibitors, and calpain inhibitors reduced IL-1a and tumor necrosis factor a mRNA levels. Hence, calpain inhibitors probably affect inhibition of signal transduction pathway rather than cleavage of IL-1a protein. As ratios of µ-calpain/calpastatin were lowest in heterozygous donors, genetically determined IL-1a levels may modulate transcription of calpain and calpastatin. This could reduce the impact of IL1A genotype on IL-1a secretion and amplify individual variation in levels generated in culture. © 2008 The Authors.